The city and its characteristics in the thought of al-Maqdisi - Al-Fahdawi, Asma Hamad Sultan; Al-Dulaimi, Kamal Abdullah Hassan (Al-Adab Journal, 2021)
the city represents one of the aspects of life that contributed to its building. Rather , the city is civilization , as both Bodlink and schengler see it , as civilization requires stability in order for a person to be liberated from the factors of volatility dispersion and the motives of anxiety , and all this is only done in the city , according to the Arabic linguistic dictionaries the city is the place in which it is established and which has fixed boundaries , and this meaning is matched by other expressions similar to it , which are maser , the present and the city , albeit to a lesser degree , and because the city has great importance in the Holy Qur’an and the noble hadiths of the prophet , Al-Maqdisi talked about it in detail in terms of meaning , distribution , classification , constituents and functions morphology and types of cities according to the functions they perform , the sizes of the cities , and the ways of differentiating between the village and the city . due to his extensive talk about medina, the Book of Best Taksim fi Knowing the Regions describes it as a study of human geography with distinction. Al-Maqdisi detailed in his discussion of the city several matters related to the position, location, extent, and land uses therein, as well as their size and spatial distribution. with dealing with customs, traditions, holidays and events. he also talked about building styles architecture, materials used in construction, street extension and directions, and areas between the city.